EVALUATION OF ANTIBIOTIC USAGE IN ISKEMIC STROKE PATIENTS WITH INFECTIONS IN RSUP DR. KARIADI SEMARANG PERIOD 2018 - Shafa Nahdah Wibowo; Trianggoro Budisulistyo; Endang Sri Sunarsih; Yora Nindita (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Abstract Background: According to WHO stroke is the second leading cause of death in the world. Ischemic stroke is the type of stroke with the highest population reaching (80%). Data at RSUP Dr. Kariadi in 2015 showed that the most common complication in stroke was infection (37.9%). The most common cause of infection was bacteria with antibiotics as the main therapy. It is necessary to monitor the use of antibiotics due to increased cases of antibiotic resistance.Objective: To determine the rationality of antibiotic use in ischemic stroke patients with infections in RSUP Dr. Kariadi Semarang Period 2018..Method: This research is a descriptive observational study. The sample consisted of 41 medical records of inpatient male ischemic stroke patients at RSUP Dr. Kariadi Semarang in 2018. The use of antibiotics was evaluated using the Gyssens method.Results: The results of evaluation of antibiotics by the Gyssens method showed antibiotic rationality (53%). The most widely used antibiotics are ampicillin sulbactam (30.4%) and levofloxacin (27.5%). Giving empirical therapy (57.5%), and diagnosis of infection in patients including pneumonia (50,8%), sepsis (19.3%), UTI (17.5%), pressure sores (5.3%), abscesses mandible (3.5%), ulcerative colitis (1.7%), cellulitis (1.7%), gasteroeneritis (1.75%).Conclusion: The use of antibiotics in ischemic stroke patients hospitalized in RSUP. Dr. Kariadi Semarang in 2018 is rational. Its users have the right antibiotics, indications, dosage, administration, route, time, interval and patient.